2015
DOI: 10.1189/jlb.4a0415-168rr
|View full text |Cite
|
Sign up to set email alerts
|

Marked alterations of neutrophil functions during sepsis-induced immunosuppression

Abstract: Severe septic syndromes deeply impair innate and adaptive immunity and are responsible for sepsis-induced immunosuppression. Although neutrophils represent the first line of defense against infection, little is known about their phenotype and functions a few days after sepsis, when the immunosuppressive phase is maximal (i.e., between d 3 and 8). The objective of the present study was to perform, for the first time, a global evaluation of neutrophil alterations in immunosuppressed septic patients (at d 3-4 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
126
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(132 citation statements)
references
References 22 publications
(24 reference statements)
5
126
1
Order By: Relevance
“…Neutrophils are the first defensive line of immune cells against bacterial pathogen infection [3, 12, 13]. Neutrophils can eliminate pathogens by phagocytosis, degranulation and neutrophil extracellular traps (NETs) when recruited to the infectious foci [1416].…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are the first defensive line of immune cells against bacterial pathogen infection [3, 12, 13]. Neutrophils can eliminate pathogens by phagocytosis, degranulation and neutrophil extracellular traps (NETs) when recruited to the infectious foci [1416].…”
Section: Discussionmentioning
confidence: 99%
“…The localization of activated neutrophils within organs contributes to organ failure in sepsis. After 3–6 days patients develop an immunosuppressive state, including impaired neutrophil chemotaxis, reduced expression of plasma membrane receptors, impaired azurophilic and specific granule mobilization, and reduced oxidative burst …”
Section: Participation Of Neutrophil Granule Mobilization In Diseasementioning
confidence: 99%
“…The increase in CD10 activity reduces the concentration of these peptides and, consequently, the inflammatory process. Some studies on CD10 expression in infectious processes demonstrate a decline in CD10 expression in septic patients (23,24). In the study by Bae et al (2016), an increase in CD10 expression was observed in sepsis survival patients when compared with expression at diagnosis, while in nonsurvival patients CD10 expression remained low and stable.…”
Section: Discussionmentioning
confidence: 87%